The Whiteface and the Auguste: the integration of structure and spontaneity in contemporary clown theatre performance - Van Wyk, Klara (Department of Drama, 2016)
This dissertation proffers argument which attempts to suggest that the consideration of both spontaneity and structure is paramount in the creation, rehearsal and performance of clown theatre. In my view, the Whiteface and Auguste clown partnership arguably represents a break in the tradition of circus clowns towards a more modern way of understanding and thinking about clowning informed by ideas around spontaneity and structure. The characteristics of their partnership are examined as possibly containing valuable insights around these concepts which may enhance our understanding of clown theatre. The dissertation is divided into three chapters. The first relies on theoretical enquiry informing my ideas around definitions and the history of the Whiteface and Auguste clowns. In the second chapter I discuss rehearsing and training for clown theatre where I engage with the contrasting clown methodologies of two practitioners, Phillipe Gaulier and Ira Seidenstein, whose clown courses I attended and whose notions I use as the framework informing my research. In the third chapter my research methodology relies heavily on practice as research conducted through three different practical projects over the two year research period. Through practical and theoretical research, the study clarifies the predominance of the Auguste clown as a way of understanding modern clowning. It aims to illuminate the way in which clowning is detrimentally emphasised as a purely spontaneous form, avoiding critical examination, and how this understanding of the clown results in an emphasis on spontaneity and games in the teaching and learning of clowning. The study argues for the significance of the Whiteface clown with regards to order, form, rules, preparation and critical enquiry. These findings both in practice and theory have provided clarity and a strong theoretical foundation from which I can attempt to create and perform in clown theatre performances where there is possibly a balance of qualities representing both the Auguste and the Whiteface figures: both structure and spontaneity.